European vocational education and training: a prerequisite for mobility? - Rauner, Felix [Verfasser] (My University, 2008)
"The purpose of this paper is to demonstrate that the internationalisation of nearly all spheres of society and the process of European integration will be leading to the development of a European vocational education and training (VET) architecture. The analysis of the 'Copenhagen process' is based on the EU documents on the realisation of a European Qualifications Framework and a credit transfer system. Findings -- The result of the study shows that the strategy adopted by the European Union for the establishment of a European area of vocational education is confronted with a dilemma. The European Qualifications Framework is highly abstract since any reference to real educational programmes and qualifications and any concrete provision for the transition and for the transferability between educational levels and sectors (vocational and higher education, initial and continuing training) was avoided in order to adhere to the anti-harmonisation clause. The result is an abstract, hierachically structured one-dimensional qualifications framework that lacks any reference to existing VET systems and that contradicts all scientific insights from VET research and knowledge research." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; L 1.3 Curriculumentwicklung; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; G 1.3.3.3 Mobilität; I 2.2 Europa; Berufsbildung; Europäischer Qualifikationsrahmen; Europäischer Bildungsraum; Curriculumentwicklung; Durchlässigkeit im Bildungssystem; Berufliche Mobilität; Europa